(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper, the qualifications considered essential by teaching professionals to be effective in pedagogical and didactic work are put together based on the results of a national survey carried out in Greece, to which secondary education teachers of all subjects contributed. One of the aims of this study was to systematically record the qualifications deemed essential by teachers for them to successfully perform their pedagogical and didactic duties. The findings of this research verify the conclusions reached in related literature regarding a holistic approach to the tools making up the profile of a “good teacher”, as most teachers seem to associate their effectiveness at work with both personal traits and “didactic and pedagogical skills”, as well as pedagogical knowledge. These particular findings contributed to a systematic and analytical description of the content of professional knowledge required for the successful performance of a teacher’s pedagogical and didactic work. Instruction furnishes a person with the capacity to adapt to the requesting circumstances of life. Training is neither just a way to gain employment, nor a nursery of considerations or a school of citizenship.